Making the case for oracy skills in higher education: practices and opportunities - Heron, Marion (Journal of University Teaching and Learning Practice, 2019)
In this paper I make the case for embedding oracy practices in the HE curriculum through explicit teaching of oracy skills and a shared common language to describe these skills. Active learning and teaching approaches as well as growing expectations of graduate employability skills have resulted in greater demands on students in UK higher education in terms of their oracy (speaking and listening) skills. Whilst oracy skills have long been the focus of studies in compulsory educational contexts, there is little transfer of research findings to a higher education context. With the aim of opening up the discussion on oracy skills in HE, this paper reports on an exploratory study carried out to investigate how teachers on two undergraduate business modules incorporated oral communication skills in their content, pedagogy and assessment. Data were gathered from observations of lectures and seminars, course documents, and semi-structured interviews with tutors. With reference to an Oracy Skills Framework the paper concludes with suggestions for how oracy skills may be more explicitly embedded into the undergraduate curriculum.